Bactericidal and virucidal mechanisms in the alkaline disinfection of compost using calcium lime and ash. (1st October 2016) - Hijikata, Nowaki; Tezuka, Rui; Kazama, Shinobu; Otaki, Masahiro; Ushijima, Ken; Ito, Ryusei; Okabe, Satoshi; Sano, Daisuke; Funamizu, Naoyuki
Abstract: In the present study, the bactericidal and virucidal mechanisms in the alkaline disinfection of compost with calcium lime and ash were investigated. Two indicator microorganisms, Escherichia coli and MS2 coliphage, were used as surrogates for enteric pathogens. The alkaline-treated compost with calcium oxide (CaO) or ash resulted primarily in damage to the outer membrane and enzyme activities of E. coli . The alkaline treatment of compost also led to the infectivity loss of the coliphage because of the partial capsid damage and RNA exteriorization due to a raised pH, which is proportional to the amount of alkaline agents added. These results indicate that the alkaline treatment of compost using calcium oxide and ash is effective and can contribute to the safe usage of compost from a mixing type dry toilet. Highlights: Calcium oxide and ash are effective as alkaline agents for compost disinfection. Alkaline-treatment impairs outer membrane and enzyme activities of E. coli. Alkaline-treatment causes partial capsid damage and RNA exteriorization of coliphage.